Prolonged Shedding of Human Parechovirus in Feces of Young Children after Symptomatic Infection. Issue 5 (May 2016) - Wildenbeest, Joanne G.; Benschop, Kimberley S.M.; Bouma-de Jongh, Saskia; Wolthers, Katja C.; Pajkrt, Dasja
Abstract : After symptomatic human parechovirus (HPeV) infection in infants, the duration of (mostly asymptomatic) shedding in feces was 2–24 weeks (median 58 days). HPeV cycle threshold value could neither differentiate between symptomatic disease and asymptomatic shedding nor between severe and mild disease as high cycle threshold values (indicating low viral loads) were observed in HPeV3-infected children with severe disease.